Plasticity and swell-shrink behaviour of electrokinetically stabilized virgin expansive soil using calcium hydroxide and calcium chloride solutions as cationic fluids = Plastyczność i kurczenie się gleby w stabilizacji elektrokinetycznej z wykorzystaniem wodorotlenku wapnia i chlorku wapnia jako płynów kationowych - James, Jijo; James, Archana; Kumar, Arun; Gomathi, Elumalai; Prasath, Karunakaran Kamal (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This investigation focussed on the plasticity and swell-shrink behaviour of an expansive soil that was stabilized using electro kinetic stabilization (EKS) techniques with cationic fluids for enhancement of stabilization. 0.25 M solutions of calcium hydroxide and calcium chloride were used as cationic fluids. An electro kinetic (EK) cell of dimensions 500 mm x 150 mm x 160 mm with inert graphite electrodes of size 140 mm x 160 mm x 5 mm was adopted for the stabilization process, carried out at an applied voltage of 40 V over a period of 6 hours.
Keywords: soil; electro kinetic stabilization; cationic fluid; plasticity; swell-shrink; calcium chloride; calcium hydroxide; gleba; stabilizacja elektrokinetyczna; płyn kationowy; plastyczność; kurczliwość pęcznienia; chlorek wapnia; wodorotlenek wapnia